2021
DOI: 10.5603/fm.a2020.0102
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric study of the thoracolumbar spine spinous process and lamina space in the Chinese

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Similar to the findings in this study, some studies report that the lowest LSP value is at the L5 vertebra [ 4 , 15 , 24 ]. Other studies report the highest LSP value at the L3 vertebra [ 16 , 18 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar to the findings in this study, some studies report that the lowest LSP value is at the L5 vertebra [ 4 , 15 , 24 ]. Other studies report the highest LSP value at the L3 vertebra [ 16 , 18 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the findings in this study, some studies report that the lowest LSP value is at the L5 vertebra [ 4 , 15 , 24 ]. Other studies report the highest LSP value at the L3 vertebra [ 16 , 18 , 24 ]. Cai et al [ 14 ] found the highest LSP value at L3 vertebra in males and L4 vertebra in females.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations